2023
DOI: 10.1371/journal.pgph.0001234
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among persons receiving tuberculosis treatment in Itezhi-Tezhi District of Zambia: A retrospective cohort study

Abstract: Itezhi-Tezhi District in southern Zambia has been reporting tuberculosis (TB) mortality rates that are fourfold higher than the national average of six percent. We conducted a retrospective cohort study to establish the demographic and clinical characteristics associated with mortality among persons under treatment for TB in Itezhi-Tezhi District, as well as the likely causes and time to death. We reviewed medical records for persons with TB registered in 19 public health facilities in Itezhi-Tezhi District be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 8 publications
1
0
0
Order By: Relevance
“…There was no record of a treatment default in this study. The mortality rate (9.9%) in this study is comparable to that found in the study in Jos Nigeria [ 36 ] but lower than that reported in Zimbabwe, 26.4% [ 30 ]; Sierra Leone, 20.5% [ 38 ]; Uganda, 18.4% [ 43 ]; and Zambia, 16.7% [ 50 ]. The disparity in treatment outcomes between these studies may be due to differences in the study population’s age, gender, and disease severity, the existence of comorbid conditions, tobacco use, the drug resistance pattern, social determinants of health, and socioeconomic characteristics [ 51 ].…”
Section: Discussionsupporting
confidence: 80%
“…There was no record of a treatment default in this study. The mortality rate (9.9%) in this study is comparable to that found in the study in Jos Nigeria [ 36 ] but lower than that reported in Zimbabwe, 26.4% [ 30 ]; Sierra Leone, 20.5% [ 38 ]; Uganda, 18.4% [ 43 ]; and Zambia, 16.7% [ 50 ]. The disparity in treatment outcomes between these studies may be due to differences in the study population’s age, gender, and disease severity, the existence of comorbid conditions, tobacco use, the drug resistance pattern, social determinants of health, and socioeconomic characteristics [ 51 ].…”
Section: Discussionsupporting
confidence: 80%
“…Although Zambia is among the high-burden countries in Southern Africa that have recorded an impressive reduction in TB mortality rate from 228 per 100,000 populations in 2000 to 86 per 100,000 populations in 2020, this rate remains high [ 1 , 3 ]. Further, the TB program conducted an epidemiological review of their routine programme data in 2020 which revealed that since 2013, the mortality rate for all forms of TB has been oscillating around 6%, ranging from 3.3% for Lusaka Province, the country’s largest and capital city, to as high as 13.6% for Southern Province [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with increased odds of mortality among people with TB include age of 65 years and above, being retreated for TB, being HIV-positive, having unknown HIV status, clinical diagnosis, and extra-pulmonary TB (EPTB) [ 3 , 7 , 13 ]. Mortality has also been found to be higher among persons with EPTB, women and undernourished persons [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations